2009
DOI: 10.1063/1.3101146
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of the stability of bubble train flow in a square minichannel

Abstract: The stability of a train of equally sized and variably spaced gas bubbles that move within a continuous wetting liquid phase through a straight square minichannel is investigated numerically by a volume-of-fluid method. The flow is laminar and cocurrent upward and driven by a pressure gradient and buoyancy. The simulations start from fluid at rest with two identical bubbles placed on the axis of the computational domain, the size of the bubbles being comparable to that of the channel. In vertical direction, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Nowadays, standard CFD codes are able to dynamically describe the interface in immiscible flows in mini channels by consideration of surface tension force and wall adhesion. [17,18,23,24] The implementation (Eqns (9) and (12)) provides so-called dynamic boundary conditions for the adjustment of the curvature of the interface near solid walls and therefore explains the deviation of apparent contact angles on the walls in relation to the SCA in our studies (Table 3). [23] In order to correctly model the physical motion of the contact line between three phases (here gas-liquid-solid) depending on the wall boundary conditions, additional user effort is needed to implement the required boundary condition into codes; e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, standard CFD codes are able to dynamically describe the interface in immiscible flows in mini channels by consideration of surface tension force and wall adhesion. [17,18,23,24] The implementation (Eqns (9) and (12)) provides so-called dynamic boundary conditions for the adjustment of the curvature of the interface near solid walls and therefore explains the deviation of apparent contact angles on the walls in relation to the SCA in our studies (Table 3). [23] In order to correctly model the physical motion of the contact line between three phases (here gas-liquid-solid) depending on the wall boundary conditions, additional user effort is needed to implement the required boundary condition into codes; e.g.…”
Section: Discussionmentioning
confidence: 99%
“…[17] The latter was verified by experimental observations of a bubble train flow. [18] There, it was found that, for the determination of the interface between gas and liquid phases, the recommended method is VOF in combination with the geometrical reconstruction method, both available in the FLUENT commercial code. This is why we used in this study again the ANSYS FLUENT system with VOF to evaluate the bubble formation in our microreactor.…”
Section: Numerical Approachmentioning
confidence: 99%
“…Liu and Wang (2008) extended this study to vertical square and equilateral triangular channels with 1 mm hydraulic diameter. Wörner and coworkers performed comprehensive numerical simulations of concurrent upward and downward Taylor flow in millimeter sized square vertical channels with an in-house PLIC-VOF code (Ghidersa et al 2004;Wörner et al 2005;Wörner et al 2007;Ö ztaskin et al 2009;Keskin et al 2010). The use of periodic boundary conditions in the axial direction allowed restriction of the computational domain to a single flow unit cell (which consists of one bubble and one liquid slug).…”
Section: Segmented Flowmentioning
confidence: 99%
“…Oztaskin et al [45] demonstrated that as the slug lengths is equal to or lower than the channel diameter, Taylor flow is not stable because the velocity profile in the liquid slug is not fully developed. The non-stable Taylor flow result in bubble coalescence.…”
Section: Comparison To Single Channel -Bubble Generation Frequency Anmentioning
confidence: 99%
“…As the liquid film thickness decreases and because there are sharp bends in the transport channels and reaction channels (see Figure 5), it is possible that partially dry walls could form. The partially dry walls can induce bubble coalescence especially at lower slug lengths (when the length is similar or lower than the channel diameter [45]). Bubble coalescence generate pressure fluctuating over the reaction channels (σ(q C ) increase) and produces larger flow non-uniformity.…”
Section: Stainless Steel Plate Reactor -Effect Of Physical Propertiesmentioning
confidence: 99%